The Dialogue Between Believers and Atheists: the Platonic Model in the Laws - Baliukonis, Simonas (Problemos, 2021)
This paper examines the question concerning the right model of epistemically rational dialogue. First of all, the main, though not undisputed, principles of rational dialogue are defined according to the contemporary field of the epistemology of disagreement. It then explains why even these principles are not sufficient for making the disagreement between believers and atheists not only a rational discourse but also a fruitful dialogue. This paper defends a thesis that the latter aim can be achieved with a proper model of dialogue, which is found in Plato’s Laws – one of the first discussions between the believers and the atheists in the Western intellectual tradition. This model not only includes the contemporary principles of rational argument but also provides some new guidelines for the solution of problems that lead the believers and the atheists to the communicational dead end.